2011
DOI: 10.1037/a0024745
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an appearance-related smoking intervention.

Abstract: This study suggests that an appearance-related smoking intervention may be a useful adjunct to traditional cessation programs with young women smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
0
30
1
Order By: Relevance
“…Findings extend beyond existing studies that have assessed outcomes using theory of planned behaviour assessments (Flett et al, 2013;Grogan et al 2011), providing some suggestions for mechanisms that may influence positive behavioural intentions towards quitting smoking following the intervention.…”
Section: Links With Previous Workmentioning
confidence: 57%
“…Findings extend beyond existing studies that have assessed outcomes using theory of planned behaviour assessments (Flett et al, 2013;Grogan et al 2011), providing some suggestions for mechanisms that may influence positive behavioural intentions towards quitting smoking following the intervention.…”
Section: Links With Previous Workmentioning
confidence: 57%
“…Grogan et al 21 conducted a randomised control trial (RCT) in order to assess the effectiveness of an age-progression intervention with women smokers. APRIL Age Progression Software V.2.5 was used in the study.…”
Section: Resultsmentioning
confidence: 99%
“…This is in keeping with previous studies on photoageing technology. 11,12 The small sample size and high rates of attrition had serious implications on our study's findings. We found that photoageing technology did not increase the number of quit attempts made by young adult smokers admitted to hospital.…”
Section: Researchmentioning
confidence: 97%
“…[7][8][9] However, a novel intervention using photoageing technology has been shown to be an effective trigger for behavioural change. 10,11 The intervention involves taking a picture of the participant's face, and digitally ageing the image through the use of wrinkling/ageing algorithms to produce a picture of the participant as an aged smoker. When implemented in a community pharmacy setting, the intervention reduced nicotine dependence and produced significantly more quit attempts when compared to smoking cessation advice alone.…”
Section: Researchmentioning
confidence: 99%